ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PROFITABILITAS PERBANKAN (STUDI PADA BANK UMUM SWASTA NASIONAL DEVISA GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018) - Adhira Rizky Pradina; Saryadi Saryadi (Universitas Diponegoro, 2019)
Return On Assets (ROA) is a profitability ratio to measure the ability of banks to generate profits so that the greater the ratio of ROA, the better performance of the bank. ROA at the national private commercial bank go public banks listed on the IDX continues to experience fluctuations from 2014 to 2018. This fluctuation can be caused by several factors. The ratios that are thought to affect profitability are CAR, LDR, NPL, NIM and BOPO. The purpose of this study was to determine the effect of CAR, LDR, NPL, NIM and BOPO on ROA. This type of research is explanatory research. The population of this study were 23 national public private banks that went public on the Indonesia Stock Exchange from 2014 to 2018. The analysis technique used was factor analysis, factor analysis, coefficient of determination test, regression analysis, and significance test using SPSS 21 data processing applications. Based on the results of the analysis it can be concluded that CAR and LDR have no effect on ROA. NPL has a negative and significant effect on ROA. NIM has positive and significant effect on ROA. BOPO has a negative and significant effect on ROA. From the results of this study, the NPL variable has the most influence on ROA so it is expected that banks will supervise and monitor the use of credit funds to avoid non-performing loans or bad loans.